A Textbook Evaluation of “My Next Words” Grade 1: A Qualitative Content Analysis Using Tomlinson’s Framework - Defi Ela Safitri; Nur Lutfiah; Rahmahdalena Putri Khairunnisa (Institut Agama ISlam Negeri Palangka Raya, 2025)
Teaching materials serve as a bridge that connects theory and practice in language learning. In other words, teaching materials are created by prioritizing the developers' belief in effective language acquisition methods, which rely on targeted exposure and activities. This study aims to evaluate the content of the English textbook for grade 1 elementary school entitled